Physical fatigability and muscle pain in patients with Hashimoto thyroiditis - Jordan, Berit; Uer, Önör; Buchholz, T.; Spens, Antje; Zierz, Stephan (Journal of neurology, 2021)
Fatigability; Fatigue; Hashimoto thyroiditis; Linear trend; Pain